AmiD Is a Novel Peptidoglycan Amidase in Wolbachia Endosymbionts of Drosophila melanogaster - Wilmes, Miriam; Meier, Kirstin; Schiefer, Andrea; Josten, Michaele; Otten, Christian F.; Klöckner, Anna; Henrichfreise, Beate; Vollmer, Waldemar; Hoerauf, Achim; Pfarr, Kenneth (Frontiers in Cellular and Infection Microbiology, 2017)
Wolbachia endobacteria are obligate intracellular bacteria with a highly reduced genome infecting many arthropod and filarial species, in which they manipulate arthropod reproduction to increase their transmission and are essential for nematode development and survival. The Wolbachia genome encodes all enzymes required for the synthesis of the cell wall building block lipid II, although a peptidoglycan-like structure has not been detected. Despite the ability to synthesize lipid II, Wolbachia from arthropods and nematodes have only a subset of genes encoding enzymes involved in the periplasmic processing of lipid II and peptidoglycan recycling, with arthropods having two more than nematodes. We functionally analyzed the activity of the putative cell wall hydrolase AmiD from the Wolbachia endosymbiont of Drosophila melanogaster, an enzyme not encoded by the nematode endobacteria. Wolbachia AmiD has Zn2+-dependent amidase activity and cleaves intact peptidoglycan, monomeric lipid II and anhydromuropeptides, substrates that are generated during bacterial growth. AmiD may have been maintained in arthropod Wolbachia to avoid host immune recognition by degrading cell wall fragments in the periplasm. This is the first description of a wolbachial lipid II processing enzyme in the periplasm.